2016
DOI: 10.1038/ncomms10795
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic ash melting under conditions relevant to ash turbine interactions

Abstract: The ingestion of volcanic ash by jet engines is widely recognized as a potentially fatal hazard for aircraft operation. The high temperatures (1,200–2,000 °C) typical of jet engines exacerbate the impact of ash by provoking its melting and sticking to turbine parts. Estimation of this potential hazard is complicated by the fact that chemical composition, which affects the temperature at which volcanic ash becomes liquid, can vary widely amongst volcanoes. Here, based on experiments, we parameterize ash behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 45 publications
1
81
0
Order By: Relevance
“…Twelve deposit compositions are considered, based on those characterized by Zaleski et al and shown in Table . The Ca:Si ratios vary from 0.14 to 0.75, covering the range of many volcanic ashes and engine deposits reported in the literature . The compositions are the same as those used in a previous study on YDS, thereby allowing direct comparisons between the behaviors of the two EBC candidates .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve deposit compositions are considered, based on those characterized by Zaleski et al and shown in Table . The Ca:Si ratios vary from 0.14 to 0.75, covering the range of many volcanic ashes and engine deposits reported in the literature . The compositions are the same as those used in a previous study on YDS, thereby allowing direct comparisons between the behaviors of the two EBC candidates .…”
Section: Methodsmentioning
confidence: 99%
“…Molten deposits, generically known as “CMAS” after their primary oxide components of Ca, Mg, Al, and Si, also contain minor amounts of Fe, Ti, Na, and K oxides. Deposit compositions vary widely with geographic region and mineral source . Reactions between the molten deposit and the EBC gradually consume the coating at elevated temperature, producing phases that remain adhered to the coating and that exhibit a substantial CTE mismatch with the composite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various life‐limiting factors, the attack of TBCs by calcium‐magnesium‐alumino‐silicate (CMAS) deposits is becoming a critical issue in advanced gas turbines due to the increased inlet temperatures . CMAS deposits, which refer to the main chemical compositions of Ca, Mg, Al, and Si, are produced when siliceous minerals (sand, dust, runway debris, volcanic ash) are ingested with the intake air . Below the melting point, these contaminants only cause erosive wear or blockage of cooling holes.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that these particles can enter the hot parts of commercial jet engines and cause them to flame out and stall (Prata & Rose, ). The precise mechanisms by which engine damage is caused by ash particles are not entirely well understood, but the silicate (Si) composition of the ash and transition through a critical temperature that transforms the glassy part of the ash from solid to liquid is believed to be of primary importance (Song et al, ).…”
Section: Introductionmentioning
confidence: 99%